Spatial analysis of PM(10) and cardiovascular mortality in the Seoul metropolitan area - Lim, Yu-Ra (The Korean Society of Environmental Health and Toxicology, 2014)
OBJECTIVES: Numerous studies have revealed the adverse health effects of acute and chronic exposure to particulate matter less than 10 μm in aerodynamic diameter (PM(10)). The aim of the present study was to examine the spatial distribution of PM(10) concentrations and cardiovascular mortality and to investigate the spatial correlation between PM(10) and cardiovascular mortality using spatial scan statistic (SaTScan) and a regression model. METHODS: From 2008 to 2010, the spatial distribution of PM(10) in the Seoul metropolitan area was examined via kriging. In addition, a group of cardiovascular mortality cases was analyzed using SaTScan-based cluster exploration. Geographically weighted regression (GWR) was applied to investigate the correlation between PM(10) concentrations and cardiovascular mortality. RESULTS: An examination of the regional distribution of the cardiovascular mortality was higher in provincial districts (gu) belonging to Incheon and the northern part of Gyeonggido than in other regions. In a comparison of PM(10) concentrations and mortality cluster (MC) regions, all those belonging to MC 1 and MC 2 were found to belong to particulate matter (PM) 1 and PM 2 with high concentrations of air pollutants. In addition, the GWR showed that PM(10) has a statistically significant relation to cardiovascular mortality. CONCLUSIONS: To investigate the relation between air pollution and health impact, spatial analyses can be utilized based on kriging, cluster exploration, and GWR for a more systematic and quantitative analysis. It has been proven that cardiovascular mortality is spatially related to the concentration of PM(10).